SOCIAL AND ECONOMIC FACTORS OF COLLECTIVE MARRIAGES IN LAHORE - F. Ghaffar; Z. Shenaz (Journal of Animal and Plant Sciences, 2010)
Collective marriages are universal phenomenon and known as mass marriages. The main focus of the present research was to explore the phenomenon of collective marriages and its socio-economic factors. For this purpose, case study method was used. The in-depth interviews of the ten couples who got married through the collective marriages project since 2005 to 2007 were conducted with their full expression, emotions and comments. Besides this, parents of the girls who got married through collective marriages residing in the city Lahore were also interviewed. Collective marriages were successfully organized and gave economic benefits to many people. As it was a new concept so many people hesitated to accept it. However, it is considered as a positive step as it helped a lot to the society. Therefore, it is suggested to continue.
Keywords: Collective marriages; socio-economic factors